Resequencing of 1,143 indica rice accessions reveals important genetic variations and different heterosis patterns - Qiming Lv (Nature Portfolio, 2020)
Hybrid rice cultivars are widely planted around the world. Here, the authors resequence 1,143 indica accessions, focusing on the parents of superior hybrid rice lines in China, and reveal genetic loci that are associated with heterosis via measuring frequency of parental variation difference (FPVD).